SERAT NANAS PRABUMULIH MENUJU ZERO WASTE PRODUCTS - Wahyu Tomo, Almira Chairunissa; Rosadi, Hengky; Husen, Mohammad Saddam (Transpublika Publisher, 2023)
Raden Mas Prabu is a program that emerged from the community's commitment to strive for the best for themselves and their environment. Their unrealized potential has proven to significantly improve their living conditions, which include economic, social, cultural, and environmental aspects. Pineapple leaves, once considered agricultural waste, have now been transformed into a valuable component of zero-waste products. Raden Mas Prabu is living proof that when communities, businesses, and governments collaborate in complementary ways, they can achieve the most effective and sustainable programs for the common good.